The Effect of Talent Management on Employee Performance at the National Archives of the Republic of Indonesia (ANRI) through Employee Motivation - Debora Justice Valentina; Annisa Syafira Efrial; Ary Priambodo (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study analyzes the effect of talent management on the performance of employees at the National Archives of the Republic of Indonesia (ANRI), with employee motivation as a mediating variable. It seeks to understand how talent management and motivation interact in shaping employee performance within a government institution. Data were collected through a questionnaire distributed to 115 ANRI employees ranging from grade III-A to IV-D, who were selected purposively, using a five-point Likert scale. The data were analyzed with Structural Equation Modeling (SEM) in the AMOS program to test the direct and indirect relationships among the variables. The results show that talent management has a positive and significant effect on employee motivation, and that motivation in turn has a positive and significant effect on performance. Talent management, however, has no significant direct effect on performance, whereas employee motivation fully mediates the relationship between talent management and performance. These findings underline the importance of cultivating employee motivation as the connecting mechanism that converts talent management into improved performance. By strengthening talent management programs alongside employee motivation, government organizations can sustain their performance and competitiveness over the long term. The study offers both theoretical contributions and practical implications for developing talent management and motivation strategies in public-sector institutions.